Tatalaksana dan sistem asuhan pada penyakit alzheimer / demensia - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
The increase in the aging world population has been accompanied by a rise in age associated disorders